Pengembangan Materi Pendidikan Akidah Untuk Siswa Tingkat SMP - Achmad Fawwas Gibran; Santi Lisnawati; Akhmad Alim (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
Aqidah education still faces various challenges, including instructional materials that do not fully cover essential content, monotonous learning models, limited instructional time, and the increasing influence of contemporary ideological challenges that may weaken students’ faith. Therefore, it is necessary to develop contextual and interactive aqidah learning materials. This study aims to analyze the need for developing aqidah education materials, formulate appropriate development procedures, and produce a supplementary instructional book. The research employed a research and development method using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). The developed product was validated by subject matter, media, and language experts and tested for feasibility by aqidah or Islamic education teachers. The results indicated a very high level of validity in the aspects of content (96%), presentation (92%), graphical design (91%), and language (93%). The feasibility test conducted by teachers resulted in a score of 93%. It can be concluded that the developed supplementary aqidah book for seventh-grade junior high school students is highly valid and very feasible for use as additional learning material.